1986
DOI: 10.1172/jci112595
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of B cell activation in patients with acquired immunodeficiency syndrome and related disorders. Contribution of antibody-producing B cells, of Epstein-Barr virus-infected B cells, and of immunoglobulin production induced by human T cell lymphotropic virus, type III/lymphadenopathy-associated virus.

Abstract: Patients with acquired immunodeficiency syndrome (AIDS) and AIDS-related complex (ARC) have hyperimmunoglobulinemia and increased numbers of circulating immunoglobulin-secreting cells. In this paper, we studied the basis for this B cell hyperactivity. Limiting dilution studies of B cells from seven patients with ARC and four with AIDS revealed that some B cells spontaneously produced antibodies to human T cell lymphotropic virus, type III/lymphadenopathy-associated virus (HTLV-III/ LAV) (39:106 and 7:106 B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(38 citation statements)
references
References 46 publications
3
34
1
Order By: Relevance
“…Furthermore, there is an indirect correlation between the number of clumps per well and the scale score of the donor, indicating that the frequency of EBV transformation decreases as disease severity increases. These data are consistent with those derived by Yarchoan et al (13) using limiting dilution analysis. Analysis of Ab from ELISA-positive expanded cultures was carried out by RIP and showed that only 59% of supernatants from these cultures reacted positively by both methods.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, there is an indirect correlation between the number of clumps per well and the scale score of the donor, indicating that the frequency of EBV transformation decreases as disease severity increases. These data are consistent with those derived by Yarchoan et al (13) using limiting dilution analysis. Analysis of Ab from ELISA-positive expanded cultures was carried out by RIP and showed that only 59% of supernatants from these cultures reacted positively by both methods.…”
Section: Resultssupporting
confidence: 93%
“…B cells from HIV-infected individuals display a low level of infectability with EBV as shown in Table 2, and in experiments by Birx et al (32) and Yarchoan et al (13). This probably accounts in part for the fact that all of our stable cell lines were derived from patients in early stages of disease and that only cells from a small percentage ofpatients in these early stages (4/17 or 23%) produced stable lines.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Several possible hypotheses may be offered to explain this phenomenon: (i) detection of HIV-1-specific antibody-secreting PBMC may refiect an in vivo stimulation of the immune system by conti-nuous HIV-1 antigen, as described by David et al (1989); (ii) inactivated whole virus or HIV-1 proteins can stimulate normal B lymphocytes directly to proliferate and differentiate into antibody-secreting cells. This in vitro poiyclonal activation has been proposed to explain the spontaneous B cell activation in vivo observed in HIV-1-infected patients (Pahwa et al, 1985;Schnittman et al, 1986); and (iii) EBV and cytomegalovirus are often associated with HIV-1 infection (Fauci et al, 1984), These viruses have also been described as in vitro poiyclonal activators (Rosen et al, 1977;Akihiro et al, 1985), It has been suggested that in vivo production of these viruses might also be responsible for spontaneous immunoglobulin in vitro secretion in HIV-1-infected patients (Lane et al, 1983;Yarchoan, Redfield & Broder, 1986), In vivo poiyclonal activation is an unlikely explanation for HIV-1 -specific antibody secretion because HIV-1 poiyclonal activation has been described in vitro using higher HIV-1 antigen concentrations than those probably involved in vivo. Moreover, in vitro polycional activation by agents such as EBV and cytomegalovirus is not probable since in some HIV-1-infected haemophiliac patients seronegative for EBV and cytomegalovirus, HIV-1-specific antibody-secreting PBMC were also detected.…”
Section: Dtscusstonmentioning
confidence: 99%
“…Immune dysfunction and B cell hyperactivation in HIV infection -There are several means by which HIV infection could result in polyclonal B cell activation: (1) direct polyclonal activation of B cells by HIV or HIV superantigens (Pahwa et al 1985, Schnittman et al 1986, Yarchoan et al 1986, Berberian et al 1993, (2) chronic antigenic stimulation of B cells by HIV (Amadori et al 1989), (3) HIV infection resulting in the loss of T cell-mediated immunoregulation of EBV-positive B cells (Birx et al 1986, Martinez-Maza 1993, (4) HIV-induced over-production of IL6 and other B cell stimulatory cytokines (Rosenberg & Fauci 1990, Breen et al 1990, Birx et al 1990, Amadori et al 1991, Rieckmann et al 1991, Honda et al 1991, Martínez-Maza 1992, Macchia et al 1993, and (5) the inappropriate expression of noncognate T/B cell stimulatory molecules (Macchia et al 1991, Chirmule et al 1993. While the relative contribution of these different mechanisms to B cell hyperactivation in HIV infection has not been defined, some information is available that allows the contributions of these different mechanisms to the induction of B cell hyperactivation to be judged.…”
mentioning
confidence: 99%